Mycoplasma hominis, Ureaplasma parvum, and Ureaplasma urealyticum: hidden pathogens in peritoneal dialysis-associated peritonitis. (June 2023) - Wang, Can; Wang, Jingshuang; Yan, Juan; Chen, Feng; Zhang, Ying; Hu, Xuelian
Highlights: Mycoplasma hominis and Ureaplasma spp. can cause peritoneal dialysis-associated peritonitis. M. hominis - or Ureaplasma spp. -caused peritonitis is related to menstruation. Metagenomic next-generation sequencing can be applied to identify the pathogen in peritoneal dialysis-associated peritonitis. Intraperitoneal tigecycline can treat peritonitis caused by M. hominis or Ureaplasma spp . Abstract: Mycoplasma hominis, Ureaplasma parvum, and Ureaplasma urealyticum commonly colonize the human urogenital tract, which may cause urogenital infections. However, infection by M. hominis, U. parvum, or U. urealyticum is rarely reported in patients with peritoneal dialysis (PD)-associated peritonitis. Herein, we reported four cases of PD-associated peritonitis caused by these pathogens, along with a review of the literature. The four cases were female patients with recurrent "culture-negative" PD-associated peritonitis and were related to menstruation. M. hominis, U. parvum, or U. urealyticum was detected in the PD fluid of the patients by metagenomic next-generation sequencing. All four patients were cured by intraperitoneal tigecycline combined with oral azithromycin or minocycline. M. hominis, U. parvum, and U. urealyticum should be paid more attention in female patients with recurrent culture-negative PD-associated peritonitis, especially when the peritonitis is related to menstruation, sexual intercourse, or urogenital tract operation. Moreover, metagenomic next-generation sequencing can provide a reasonable method to identify the pathogen for culture-negative PD-associated peritonitis.